Changes of Swimmers’ Emotional States during the Preparation of National Championship: Do Recovery-Stress States Matter? - Vacher, Philippe (Front Psychol, 2017)
This study examined the trajectories of emotional states and their within-person synergies with perceived stress and recovery during a 4-month training period preceding the French swimming championships. A Multilevel Growth Curve Analysis approach was used with 16 high level swimmers. Five waves of assessments of emotional states, perceived stress and recovery were completed. Results indicated that emotional states were characterized by distinct trajectories during the training period preceding a major competition. Specifically, significant positive linear effects of time (i.e., linear increase over time) and negative quadratic effects of squared time (i.e., inverted U shape over time) on anxiety, dejection and anger were observed, whereas the opposite pattern of results was found for happiness and excitement. Moreover, level 2 perceived stress and recovery (i.e., inter-individual predictors) were significantly associated with athletes’ unpleasant and pleasant emotional states respectively. At level 1, perceived recovery (i.e., intra-individual predictor) was positively associated with happiness and excitement and negatively related to anxiety, dejection and anger. Finally, within-person interactions of general stress and recovery with time and squared time reached significance for excitement, whereas within-person interactions of specific and total stress with time and squared time reached significance for anxiety. Overall, this study provided insights into the central role played by perceived stress and recovery on the emotional states experienced by high level swimmers. Operational strategies were suggested in order to optimize the stress-recovery balance and in turn the athletes’ emotional states during a complete training program.